The Effectiveness of the Paired Reading Method in Improving Reading Literacy Comprehension for 15 Minutes in MA Al-Hikmah Madura Students - Fatima, Siti Nor; Susandi, Susandi (Syntax Corporation Indonesia, 2023)
The quality of learning will be very good if it is designed according to the characteristics and needs of students, one of which is through the double reading method. The method of reading in pairs is to encourage different thinking and understanding by reading passages in pairs to save time. Therefore, schools should implement literacy programs to increase students' interest in reading and comprehension so that students not only read but also understand what they read. The main purpose of this study was to find out whether the use of pair reading method can improve students' reading comprehension in book 4 for 15 minutes at MA Al-Hikmah Madura. The approach in this study is a quantitative approach. The type of research used is experimental research. The results of this study are the result of a separate test-count model. It is known that the average increase in the control group was 1.25 while the increase in the experimental class was 24 so that it was known that the increase in experimental class learning outcomes was greater than 22.75 compared to the administration class. It is known that the calculated t value is 2.782 with a significance of 0.009. The 16 db table t value is 0.4683. So it can be concluded that t table > t count (2.782 > 0.4683) and the significance value is smaller than 0.05 (p = 0.009 < 0.05), so it can be said that there is a significant difference in the increase in the threshold of learning. Significant results in both the control group and the experimental group. There is a significant difference between the normal learning method and the paired reading method to improve student learning outcomes in the MA Al-Hikmah Madura course